Urine citrate and 6-sulfatoximelatonin excretion during a training season in top kayakers - Nunez, P.; Diaz, E.; Terrados, N.; Diaz, B. (European Journal of Applied Physiology, 2012)
The effects of high training loads during the competitive kayaking season may be reflected in urinary citrate and 6-sulfatoxymelatonin (°MT6S) excretion. The present study aims to evaluate the influence of a training program on citrate and °MT6S excretion in 12 elite kayakers. Urine samples were collected (before bedtime and again in the morning, at first voiding) at the beginning of the season (second half of October), during the macrocycle (specific training period; first week of June), and tapering (precompetitive training period; first week of July) stages. During the training season, urine citrate values (mg/L) were higher in the evening than in the morning in all stages (p < 0.01). The data obtained in the evening showed the lowest significant values (p < 0.05) in the beginning stage compared with the macrocycle and tapering stages. The values obtained in the morning showed the lowest significance (p < 0.05) in the macrocycle stage compared to the beginning and the tapering stages. In all stages, °MT6S (ng/mL) evening values were significantly lower (p < 0.05) than the morning values. The morning/evening ratio, total sum, and nocturnal increment of °MT6S did not vary across the training stages. From these results, it can be deduced that the pineal function is unaltered and that citrate turnover is good in elite kayakers during the training season. It was found that urine citrate and °MT6S obtained by non-invasive techniques may be used as major markers to evaluate metabolic recovery and stress produced by the training season workload in elite kayakers.